The Addition of Other Fecal Biomarkers Does Not Improve the Diagnostic Accuracy of Immunochemical Fecal Occult Blood Test Alone in a Colorrectal Cancer Screening Cohort - Hijos-Mallada, Gonzalo; Lué, Alberto; Velamazan, Raul; Saura, Nuria; Abril, Carlos; Lorenzo, Marta; Navarro, Mercedes; Chueca, Eduardo; Arechavaleta, Samantha; Gomollón, Fernando; Lanas, Ángel; Sostres, Carlos (Frontiers in Medicine, 2021)
Background: Screening with fecal occult blood test reduces colorectal cancer (CRC) incidence and mortality, and is currently implemented in most countries. However, around 40% of screening colonoscopies are normal. Thus, strategies to avoid these colonoscopies are highly necessary. Adding other fecal biomarkers, such as fecal calprotectin (FC), lactoferrin, and transferrin may be useful, but evidence is scarce. Aims: To evaluate the diagnostic accuracy of fecal occult blood immunochemical test (FIT), FC, and a one-step combo card test for the simultaneous semi-qualitative detection of human hemoglobin (hHb), transferrin (hTf), calprotectin (hCp) and lactoferrin (hLf) in a CRC screening program population. Methods: Single-center, prospective observational study, enrolling patients included in a CRC screening program, referred for a colonoscopy due to a positive FIT test. Participants collected a stool sample prior to bowel preparation, and FIT, FC and the combo semi-qualitative tests were performed on the sample. Sensitivity, specificity, positive and negative predictive values and area under receiver operator curve (AUC) for diagnosis of advanced neoplasia, advanced adenoma and CRC were estimated for each biomarker and their combinations. The primary endpoint of the study was to assess whether these biomarkers could improve the diagnostic accuracy of FIT alone. Results: 336 consecutive patients (64% males) were recruited. Advanced neoplasia was found in 129/336 (38.4%) patients, and of these, 22/336 (6.5%) were diagnosed of CRC. 153/336 (45.5%) colonoscopies were completely normal. The AUC for the diagnosis of advanced neoplasia were 0.725 (95%CI 0.665–0.784) for FIT, 0.477 (95%CI 0.413–0.541) for FC and 0.732 (95%CI 0.674–0.791) for the combination of both (FIT + FC) quantitative tests. The AUCs for the combo test were 0.70 (95%CI 0.641–0.760) for hHb, 0.625 (95%CI 0.562–0.698) for hTf, 0.532 (95%CI 0.469–0.595) for hCp, 0.531 (95%CI 0.466–0.595 ) for hLf and 0.681 (95%CI 0.620–0.741) for the combination of the four biomarkers. Conclusion: In average-risk population, FIT appears to be the best fecal marker for the diagnosis of CRC and advanced adenoma. None of the other biomarkers explored or their combinations provided a better diagnostic accuracy. Only hTF showed an acceptable diagnostic accuracy. FC and hLF were not useful in this setting.